The Influence of Advertising and Personal Selling on Buying Interest - Adi Utama (Almana : Jurnal Manajemen dan Bisnis, 2020)
Clothing is very popular these days. Advertising and Personal Sales are very important for companies to promote and influence people to be interested in buying products. The purpose of this study is to determine the effect of advertising on interest, to determine the effect of personal selling on buying interest, and to determine the effect of advertising and personal selling on Dr. Ricks Denim. The research method used is descriptive verification, a population of 19,500 people, with a sample of 100 respondents. The data analysis method uses multiple regression analysis and hypothesis testing. The results obtained from advertising affect buying interest in Dr. Ricks Denim. Overall respondents indicated that Dr. Ricks Denim Advertising still needs to be improved because there are still some ranks below the average such as information about product clothing models, clothing sizes according to information. Personal sales affect Dr. buying interest Ricks Denim. Overall respondents are considered quite good, this shows that Personal Selling still needs to be improved because there are still a number of ratings below the average. Advertising and personal selling affect Dr.'s buying interest Denim Ricks simultaneously show that Ho was rejected. Thus Personal Advertising and sales can increase consumer buying interest.